ПРОБЛЕМА ІНСТИТУАЛІЗАЦІЇ КУРСІВ З ТЕНДЕРНИХ ПИТАНЬ У ПРАКТИКУ ВИЩОЇ ШКОЛИ (Педагогіка вищої та середньої школи, 2004)
The article is devoted to the problem ofproviding of gender awareness into the practice of higher school The author underlines the importance of interdisciplinary specificity of gender component. He characterizes the factors, which influence on the contemporary situation of the problem of higher school in Ukraine.